Positron emission particle tracking : a comprehensive guide - Windows-Yule, Kit; Nicuşan, Leonard; Herald, Matthew T.; Manger, Samuel; Parker, David (David J.) (IOP (Series). Release 22., 2022)
Positron Emission Particle Tracking (PEPT) is a technique which allows the three-dimensional, internal dynamics of opaque systems to be imaged with high temporal and spatial resolution. This book provides both an accessible introduction to, and a comprehensive reference guide for the PEPT technique.